Empathetic remote death notification in the context of Covid-19 - Edgar Landa-Ramírez; Nadia Alejandra Domínguez-Vieyra; Myriam Eunice Hernández-Núñez; Lesly Pamela Díaz-Vásquez (Instituto Nacional de Salud Pública, 2020)
Not available